(untitled) (Scientific journal of the Fergana State University, 2024)
This article covers the problem of helminths, their appearance and effect on the organism of birds and poultry. The parasite is related to the relationship between the organism and the environment, the dependence of the parasite fauna on food, geographical zoning, the anthropogenic factor, human economic activity, and other environmental factors. Extensive research conducted by scientists determined the scientific foundations of ecological parasitology and the directions of the field.